Ни любви, ни роботов - Голиков Артем Викторович (Серия "Одобрено Рунетом", 2022)
Содержит нецензурную брань Экземпляры: ЦБ (20230508) / Инвентарный номер: 56963 / Цена: 440.77 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Г 60 / ГРНТИ: 17.82.32 / ББК: 84(2=411.2)6-44